2010
DOI: 10.1111/j.1469-1795.2009.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Pest reduction services by birds in shade and sun coffee in Jamaica

Abstract: The reduction of insect pests by birds in agriculture may provide an incentive for farming practices that enhance the conservation value of farms for birds and other wildlife. We investigated pest reduction services by insectivorous birds on a coffee farm in Jamaica, West Indies. Our results suggest that birds reduced insect pests on our study site. Infestation by the coffee berry borer Hypothenemus hampei, the world's most damaging insect pest in coffee, was significantly elevated on coffee shrubs from which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(120 citation statements)
references
References 35 publications
2
113
2
3
Order By: Relevance
“…Alternatively, higher pest removal with increasing shade cover may be due to a functional response, whereby birds are more likely to detect and consume large and profitable prey like caterpillars when they can search for them from above. However, this finding differs from other studies that found no relationship between avian pest control and any measures of vegetation complexity, including canopy cover (Kellermann et al 2008, Philpott et al 2009) or actually found a negative correlation with vegetation complexity (Johnson et al 2010). Even so, the most comparable study examining the removal of lepidopteran larvae also found a positive relationship between canopy cover and pest removal (Perfecto et al 2004), whereas studies that found no relationship examined predation of coffee berry borer (Kellermann et al 2008, Philpott et al 2009).…”
Section: Modelcontrasting
confidence: 55%
See 1 more Smart Citation
“…Alternatively, higher pest removal with increasing shade cover may be due to a functional response, whereby birds are more likely to detect and consume large and profitable prey like caterpillars when they can search for them from above. However, this finding differs from other studies that found no relationship between avian pest control and any measures of vegetation complexity, including canopy cover (Kellermann et al 2008, Philpott et al 2009) or actually found a negative correlation with vegetation complexity (Johnson et al 2010). Even so, the most comparable study examining the removal of lepidopteran larvae also found a positive relationship between canopy cover and pest removal (Perfecto et al 2004), whereas studies that found no relationship examined predation of coffee berry borer (Kellermann et al 2008, Philpott et al 2009).…”
Section: Modelcontrasting
confidence: 55%
“…In the few studies examining direct effects, pest control was positively associated with measures of vegetation complexity Armbrecht 2006, Armbrecht andGallego 2007), had no relationship with measures of vegetation (Kellermann et al 2008, Philpott et al 2009 or was actually negatively correlated with vegetation complexity, potentially due to higher ambient levels of pests in sun coffee (Johnson et al 2010). Coffee berry borer abundance did decrease with greater levels of forest cover on farms in Costa Rica (Karp et al 2013) and a simulation model based on data from Jamaican coffee farms found that the presence of forest patches decreased coffee berry borer infestations, but only until up to a certain amount of forested area (Railsback and Johnson 2014).…”
Section: List Of Tablesmentioning
confidence: 99%
“…High diversity and abundance of ants provide important ES in coffee agroecosystems since ants are an important predator group 235,237 . Another predator studied in the coffee agroforest, birds, helps control coffee berry borers and thus increases coffee yield and farm income, a potentially important conservation incentive for producers 238,239 . Landscape heterogeneity may allow mobile predators to provide pest control broadly, despite localized variation in farming intensities.…”
Section: Biotic Regulationmentioning
confidence: 99%
“…Experimentos realizados na América Central demonstraram claramente que a taxa de remoção de artrópodes no campo, incluindo pestes, aumenta conforme aumenta a riqueza de espécies de aves (Philpott et al 2009). Em lavouras de café também na América Central, foi demonstrado que as aves reduzem significativamente a infestação do besouro (Hypothenemus hampei) nos cafezais, uma das pragas mais danosas para essas plantações em todo o mundo (Johnson et al 2010). Esses estudos indicam que a integração da produção com a conservação da biodiversidade pode caracterizar um sistema em que todos saem ganhando.…”
Section: Considerações Finaisunclassified